2012
DOI: 10.5935/1678-9741.20120038
|View full text |Cite
|
Sign up to set email alerts
|

Heart defects treatment in Sergipe: propose of resources' rationalization to improve care

Abstract: Objective: This study aims evaluate the treatment of congenital heart disease conducted from 2000 to 2009.Methods: The sample consisted of all patients undergoing surgical correction for congenital heart disease for ten years in Sergipe, Brazil. The patients were operated in three hospitals located in the city of Aracaju, capital of the state of Sergipe (Brazil). The study was divided into two periods defined by the start date of centralization of surgery. The variables collected were: age, sex, postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The total mortality of the sample was 14.7% with an area under ROC curve for RACHS-1 score of 0.738 (95% CI 0.690 to 0.783). In Sergipe, the RACHS-1 score was used to classify 932 procedures performed, with a predominance of category 1 and 2, with a mortality of 8.3% and area under ROC curve of 0.860 (95% CI 0.818 to 0.902) in 10 years of study follow-up [ 13 ] . Jacobs et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total mortality of the sample was 14.7% with an area under ROC curve for RACHS-1 score of 0.738 (95% CI 0.690 to 0.783). In Sergipe, the RACHS-1 score was used to classify 932 procedures performed, with a predominance of category 1 and 2, with a mortality of 8.3% and area under ROC curve of 0.860 (95% CI 0.818 to 0.902) in 10 years of study follow-up [ 13 ] . Jacobs et al.…”
Section: Discussionmentioning
confidence: 99%
“… Reference Local Mortality Duration of the study (years) No. of patients ROC curve Mortality by RACHS-1 category Mattos et al [ 15 ] , 2006 PE 14.7% 5 818 _ 1 and 2 - 8.76% 3 and 4 - 26.12% 5 and 6 - 100% Nina et al [ 16 ] , 2007 MA 17.2% 3 145 _ 1 - 3.8% 2 - 26% 3 - 60% DATASUS- São Paulo, 2011 [ 17 ] SP 7.1% 1 974 _ 1 - 1.3% 2 - 5.1% 3 - 10.4% 4 - 22.5% 5 - 60% 6 - 61.1% Leite et al [ 13 ] , 2012 PE 8.2% 9 932 0.860 1 - 0.25% 2 - 6.6% 3 - 11.1% 4 - 62% 6 - 100% Cavalcanti et al [ 12 ] , 2015 PE 14.7% 4.5 360 …”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we identified a lack of studies reporting data related to hospital or operative mortality in congenital heart disease in our country over the last 10 years [ 19 - 21 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The latest publication includes results of patients operated over 4 years ago and reports 10 years of surgical treatment of congenital heart disease (including adults) in the state of Sergipe, examining differences in outcomes after the surgery centralization from three hospitals [ 21 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The twelve articles selected (6,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Regarding the place of publication of the studies, eight were international, conducted in the United States of America (USA) (23) .…”
Section: Review Studymentioning
confidence: 99%